Peran Terlipressin pada Penyakit Hati Kronik - Andrea, Decky; Rotty, Luciana (Universitas Sam Ratulangi, 2021)
Abstract: Chronic liver disease is a progressive impairment of liver function. It is caused by non-alcoholic fatty liver, viral infection of the liver, excessive alcohol consumption, metabolic diseases such as galactosemia, autoimmune disease, and the influence of chemicals. Complications that are often found are esophageal variceal bleeding, hepatorenal syndrome, and refractory ascites. Terlipressin, which is a vasopressin analogue, is currently widely used in developed countries because it has been shown to improve survival of patients with esophageal varices, hepatorenal syndrome, and refractory ascites. Terlipressin is the current standard therapy for esophageal variceal bleeding in countries where it is available.Keywords: chronic liver disease; terlipressinÂ Â Abstrak: Penyakit hati kronis (PHK) adalah gangguan fungsi hati yang terjadi secara progresif. Peyakit hati kronis di sebabkan oleh non-alcoholic fatty liver, infeksi virus pada hati, konsumsi alkohol berlebihan, peyakit metabolik seperti galaktosemia, penyakit autoimun, dan pengaruh bahan kimia. Komplikasi yang sering ditemukan pada PHK ialah perdarahan varises esofagus, sindrom hepatorenal, dan asites refrakter. Terlipressin yang merupakan analog vasopressin saat ini banyak di pakai di negara maju karena terbukti dapat meningkatkan kelangsungan hidup pasien perdarahan varises esofagus, sindrom hepatorenal, dan asites refrakter. Dewasa ini terlipressin telah menjadi terapi standar perdarahan varises esofagus di negara-negara di mana obat ini tersedia.Kata kunci: penyakit hati kronik; terlipressin